(untitled) (Research, Society and Development, 2020)
The leaves of Campomanesia sessiliflora (popularly known as guabiroba-verde) are consumed by infusion by the population, having great socioeconomic and cultural importance, in addition to impacting the health of the local population, however there are few studies regarding the biological activities of this plant, in this sense The objective was to analyze the antiproliferative and mutagenicity action in Allium cepa, as well as the chemical composition of the C. sessiliflora leaves infusion. The infusion of C. sessiliflora leaves showed 106.50 ± 10.10 mg g-1 of phenolic compounds, 47.58 ± 0.20 mg g-1 of flavonoids and 0.22 ± 0.01 mg g-1 of tannins, already in the test in A. cepa the extract did not induce the formation of micronuclei and cell death in concentrations equal to or below 0.5 mg mL-1, however with significantly lower rates than the negative control at a concentration of 1.0 mg mL-1. The results obtained indicate an antiproliferative effect depending on the concentration of the extract.